Evaluation of Bone Health in Postmenopausal Women Using Long-Term Levothyroxine Treatment Due to Post-Procedural Hypothyroidism - Apaydin M; Surel F; Kazan S (International Journal of General Medicine)
Mahmut Apaydin,1 Ferda Surel,2 Sinan Kazan3 1Department of Endocrinology and Metabolism, Afyonkarahisar Health Sciences University, Afyonkarahisar, Turkey; 2Department of Physical Medicine and Rehabilitation, Ministry of Health Ankara Bilkent City Hospital, Ankara, Turkey; 3Department of Nephrology, Afyonkarahisar Health Sciences University, Afyonkarahisar, TurkeyCorrespondence: Mahmut Apaydin, Afyonkarahisar Health Sciences University, Dörtyol 2078 Street, No: 3, Afyonkarahisar, 03030, Turkey, Tel +902722463335, Email drmahmutapaydin@gmail.comPurpose: The connection between thyroid disorders and the health of bone is an endocrinological dilemma for physicians. Several studies have been conducted to examine the correlation between levothyroxine use and the risk of fracture. Different results have been obtained in these studies. The objective of the present study is to evaluate the impact of prolonged thyroid hormone replacement therapy on bone health in postmenopausal women.Patients and Methods: We obtained demographic data, laboratory results, and anthropometric measurements of patients from the hospital database. After the exclusion of patients, 59 patients with post-procedural hypothyroidism (n = 59) and a control group (n = 45) were evaluated. The patient group consisted of individuals who had undergone thyroid surgery for a benign condition and had been on levothyroxine treatment for a minimum of 5 years. Densitometric measurements of bone mass in the hip and spine were performed by bone mineral densitometry.Results: Groups were similar in age, PTH, vitamin D, bone-specific ALP, and BMI (p> 0.05). The control group had a significantly lower total T score-F than the hypothyroidism group (− 0.77± 1.3 to − 0.29± 1.02, p= 0.041). However, total T score-LV, total gr/cm2-LV, and total gr/cm2-F were similar in both groups.Conclusion: This study showed that long-term levothyroxine therapy, which aims to maintain TSH levels within the normal reference range, is associated with increased bone mineral density (BMD) in postmenopausal women compared with the control group. Thus, to maintain bone health and prevent osteoporosis, it is important that postmenopausal women on long-term levothyroxine replacement undergo medical follow-up to prevent TSH suppression.Keywords: osteoporosis, hypothyroidism, levothyroxine, bone health, thyroid stimulating hormone, TSH